A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 2. Revision of the Craspedophorus leprieuri and C. regalis groups (Coleoptera: Carabidae) - Häckel, Martin (Zootaxa, 2017)
Afrotropical species of the Craspedophorus leprieuri and Craspedophorus regalis groups are revised. C. clasispilus (Alluaud, 1915) and C. guineensis Basilewsky, 1987 are considered as subspecies of C. leprieuri (Laporte de Castelnau, 1835); the synonymized C. peringueyi Csiki, 1929 (=laticollis Péringuey, 1904) is restated as subspecies of C. leprieuri, and it is described C. leprieuri zambianus (DR Congo: Katanga Province; Zambia); C. pseudofestivus Burgeon, 1930 is considered subspecies of C. merus Péringuey, 1904, and it is described C. merus lundanus (Angola, DR Congo: Kasai-Oriental and Katanga Provinces); C. bouvieri imperialis Burgeon, 1930 is considered to be a separate species of C. bouvieri (Rousseau, 1905), and C. bouvieri dux Basilewsky, 1951 is transferred to C. imperialis. The synonymized C. sayersii (Hope, 1842) is considered to be a good subspecies of C. regalis. C. bouvieri crampeli (Alluaud, 1915) is removed from C. bouvieri, and transferred to C. reflexus (Fabricius, 1781) in the C. reflexus species group (Häckel 2016). In this group C. uelensis Burgeon, 1930 is considered to be a subspecies of C. reflexus; and C. bozasi Alluaud, 1930 is synonymized with C. reflexus uelensis Burgeon, 1930. C. arnosti Häckel 2016 is synonymized with C. reflexus crampeli (Alluaud, 1915), C. ethmoides Alluaud, 1930 is synonymized with C. impictus (Boheman, 1848), and C. lebaudyi Alluaud, 1932 is synonymized with C. stanleyi Alluaud, 1930.